Operational Demands of AAC Mobile Technology Applications on Programming Vocabulary and Engagement During Professional and Child Interactions. (2nd January 2016) - Caron, Jessica; Light, Janice; Drager, Kathryn
ABSTRACT: Typically, the vocabulary in augmentative and alternative communication (AAC) technologies is pre-programmed by manufacturers or by parents and professionals outside of daily interactions. Because vocabulary needs are difficult to predict, young children who use aided AAC often do not have access to vocabulary concepts as the need and interest arises in their daily interactions, limiting their vocabulary acquisition and use. Ideally, parents and professionals would be able to add vocabulary to AAC technologies "just-in-time" as required during daily interactions. This study compared the effects of two AAC applications for mobile technologies: GoTalk Now (which required more programming steps) and EasyVSD (which required fewer programming steps) on the number of visual scene displays (VSDs) and hotspots created in 10-min interactions between eight professionals and preschool-aged children with typical development. The results indicated that, although all of the professionals were able to create VSDs and add vocabulary during interactions with the children, they created more VSDs and hotspots with the app with fewer programming steps than with the one with more steps, and child engagement and programming participation levels were high with both apps, but higher levels for both variables were observed with the app with fewer programming steps than with the one with more steps. These results suggest that apps with fewer programming steps may reduce operational demands and better support professionals to (a) respond to the child's input, (b) use just-in-time programming during interactions, (c) provide access to more vocabulary, and (d) increase participation.